95 [ninety-five] theses on righteousness by faith: apologies to Martin Luther - Venden, Morris L. (Pacific Press Publ. Assn., 1987)
Although, as we near time's end, "one interest will prevail, one subject will swallow up every other,--Christ our righteousness" some may not especially welcome another book on the subject of righteousness by faith.But the fact remains that no other message is more vital or more urgently needed by both the church and the world today than the good news of Christ's righteousness.95 Theses is no stuffy treatise crammed with polysyllabic theological jargon. It is instead a nuts-and-bolts exploration of the simple fundamentals of knowing and trusting Jesus.95 Theses on Righteousness by Faith is Elder Venden's most ambitious and significant book to date. It is his chief hope that readers of these pages will learn more clearly to trust Jesus Christ both pardon and power.